2020
DOI: 10.1371/journal.pone.0238632
|View full text |Cite
|
Sign up to set email alerts
|

Meconium microbiome and its relation to neonatal growth and head circumference catch-up in preterm infants

Abstract: The purpose was identify an association between meconium microbiome, extra-uterine growth restriction, and head circumference catch-up. Materials and methods: Prospective study with preterm infants born <33 weeks gestational age (GA), admitted at Neonatal Unit and attending the Follow-Up Preterm Program of a tertiary hospital. Excluded out born infants; presence of congenital malformations or genetic syndromes; congenital infections; HIV-positive mothers; and newborns whose parents or legal guardians did not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 57 publications
(75 reference statements)
1
19
0
Order By: Relevance
“…This study shows the development and diversity of the gut microbiome in 24 samples derived from the feces samples of eight preterm neonates born at CMH, Jakarta, at 3 different time points in early life. The analysis of gut microbiome development over the first week based on alpha and beta diversity in terms of relative abundance showed that for the 8 subjects providing 24 feces samples at the three time points, i.e., meconium, day 4 feces, and day 7 feces, Proteobacteria and Firmicutes were dominant at the phylum level, while at the genus level, unidentified Enterobacteriaceae were most abundant, as has been reported widely 1 , 6 , 7 , 9 , 10 , 29 34 . This result is similar to our previous study on cultivable bacteria from meconium from neonates born in CMH 9 .…”
Section: Discussionsupporting
confidence: 64%
“…This study shows the development and diversity of the gut microbiome in 24 samples derived from the feces samples of eight preterm neonates born at CMH, Jakarta, at 3 different time points in early life. The analysis of gut microbiome development over the first week based on alpha and beta diversity in terms of relative abundance showed that for the 8 subjects providing 24 feces samples at the three time points, i.e., meconium, day 4 feces, and day 7 feces, Proteobacteria and Firmicutes were dominant at the phylum level, while at the genus level, unidentified Enterobacteriaceae were most abundant, as has been reported widely 1 , 6 , 7 , 9 , 10 , 29 34 . This result is similar to our previous study on cultivable bacteria from meconium from neonates born in CMH 9 .…”
Section: Discussionsupporting
confidence: 64%
“…Another study in Brazil, compared microbiome diversity in meconium between infants with early HC catch-up growth (<6 months) and infants with late HC catch-up growth (>6 months). They reported greater microbial diversity and a higher abundance of Acinetobacter in meconium from infants with late HC catch-up growth that was independent of infant weight ( Terrazzan Nutricionist et al, 2020 ). Some of these results were consistent with our findings, as we also found HC to be associated with human milk alpha-diversity in late lactation.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital infections are a group of diseases that are present from the fetal into the early postnatal stage of life, which have been found to have adverse effects on metabolic, microbiome, and neurological development in the neonate ( Surtees et al, 1990 ; Mechtler and Kinkel, 1993 ; Terrazzan Nutricionist et al, 2020 ). TORCH is a common acronym used to refer to a set of these infections: (T)oxoplasmosis, (O)ther agents such as syphilis and parvovirus B19, Rubella, (C)ytomegalovirus infection (CMV), and (H)erpes simplex virus (HSV) ( Macedo-da-Silva et al, 2020 ; Jaan and Rajnik, 2022 ).…”
Section: Introductionmentioning
confidence: 99%